Media coverage style of global warming and level of public acknowledgement of the issue : case study on Sin Chew Jit Poh and News Straits Times in Malaysia from January 2010 to May 2010 - Soh, Lin Chai (2011)
The level of public acknowledgement of global warming issues is still relatively low although there is quite a number of news reporting on global warming have been published by traditional media. A comparative study on coverage style of Sin Chew Daily and New Straits Times (NST) from January 2010 to May 2010 on global warming issues is conducted, in which the contexts such as lexicons, leads, headlines, placements, layouts and reporting style are analyzed to determine whether there is reasonable coverage on the issues. The researcher employed judgmental sampling where news articles which related to 全球暖化 (global warming) and 气候变化 (climate change) are collected for data. The researcher found out that Sin Chew Daily commonly used feature style of news reporting while New Straits Times mainly focused on hard news coverage. Sin Chew Daily had succeeded to increase the level of public acknowledgement of global warming issues by using narrative style of reporting in most of the news coverage, and it would be more efficient in provoking the public to act against global warming when coverage are based on human interest stories.